2019
DOI: 10.1002/hbm.24874
|View full text |Cite
|
Sign up to set email alerts
|

Replicable brain signatures of emotional bias and memory based on diffusion kurtosis imaging of white matter tracts

Abstract: Diffusion MRI (dMRI) is sensitive to anisotropic diffusion within bundles of nerve axons and can be used to make objective measurements of brain networks. Many brain disorders are now recognised as being caused by network dysfunction or are secondarily associated with changes in networks. There is therefore great potential in using dMRI measures that reflect network integrity as a future clinical tool to help manage these conditions. Here, we used dMRI to identify replicable, robust and objective markers that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…More recently, studies using very large samples (i.e., the UK Biobank), as well as meta-analyses combining both published and unpublished data (i.e., the ENIGMA consortium), have observed widespread and replicable reductions in FA ( Shen et al, 2017 , van Velzen et al, 2020 ). Notably, white matter integrity in identified regions has been shown to correlate with the cognitive processes disrupted in depression, including processing speed ( Chopra et al, 2018 , Penke et al, 2010 ), emotion regulation ( Eden et al, 2015 , Welton et al, 2020 ), and reward learning ( de Boer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies using very large samples (i.e., the UK Biobank), as well as meta-analyses combining both published and unpublished data (i.e., the ENIGMA consortium), have observed widespread and replicable reductions in FA ( Shen et al, 2017 , van Velzen et al, 2020 ). Notably, white matter integrity in identified regions has been shown to correlate with the cognitive processes disrupted in depression, including processing speed ( Chopra et al, 2018 , Penke et al, 2010 ), emotion regulation ( Eden et al, 2015 , Welton et al, 2020 ), and reward learning ( de Boer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…7). 77 An assessment of cerebral tissue with diffusion kurtosis imaging revealed that emotional dysregulation was associated with increased diffusivity and reduced cellular complexity in specific regions of the temporal and parietal lobes, as well as the adjoining white matter tracts. Emotional dysregulation is a factor contributing to morbidity in postoperative cognitive dysfunction, 120 and using diffusion kurtosis imaging in the context of perioperative medicine will likely provide novel insights into the structural basis of this disease.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…75,76 Further information regarding the composition of tissue can be acquired using diffusion kurtosis imaging. This technique involves the acquisition of images at multiple magnetic field strengths to determine how diffusion of water in a given region of the brain differs from a normal Gaussian distribution 36,77 (fig. 7).…”
Section: Fig 6 (A)mentioning
confidence: 99%
“…More recently, studies using very large samples (i.e., the UK Biobank), as well as meta-analyses combining both published and unpublished data (i.e., the ENIGMA consortium), have observed widespread and replicable reductions in FA 15,16 . Notably, white matter integrity in identified regions has been shown to correlate with the cognitive processes disrupted in depression, including processing speed 20,21 , emotion regulation 22,23 , and reward learning 24 .…”
Section: Introductionmentioning
confidence: 99%